Acupuncture for treating alopecia areata: a protocol of systematic review of randomised clinical trials. Issue 10 (26th October 2015) - Lee, Hye Won; Jun, Ji Hee; Lee, Ju Ah; Lim, Hyun-Ja; Lim, Hyun-Suk; Lee, Myeong Soo
Abstract : Introduction: Acupuncture is frequently used in dermatology for treating a number of skin disorders. There is no critically appraised evidence of the potential benefits and harm of acupuncture for alopecia areata (AA). This review aims to systematically evaluate the efficacy of acupuncture for the management of AA in randomised clinical trials (RCTs). Methods and analysis: 13 databases will be searched from their inception. These include PubMed, AMED, EMBASE, the Cochrane Library, 6 Korean medical databases (Koreanstudies Information Service System, DBPIA, The Town Society of Science Technology, Research Information Sharing Service, KoreaMed and the Korean National Assembly Library), 3 Chinese Databases (China National Knowledge Infrastructure Database (CNKI), the Chongqing VIP Chinese Science and Technology Periodical Database (VIP) and the Wanfang Database). Only randomised clinical trials (RCTs) using any type of acupuncture for AA will be considered. The selection of the studies, data abstraction and validation will be performed independently by two researchers. Methodological quality will be assessed with Cochrane risk of bias. Dissemination: The systematic review will be published in a peer-reviewed journal. The review will also be disseminated electronically and in print. Updates of the review will be conducted to inform and guide the healthcare practice and policy. Trial registration number: PROSPERO 2015: CRD42015020397.